If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (u + -5) * 7 = 63 Reorder the terms: (-5 + u) * 7 = 63 Reorder the terms for easier multiplication: 7(-5 + u) = 63 (-5 * 7 + u * 7) = 63 (-35 + 7u) = 63 Solving -35 + 7u = 63 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + 7u = 63 + 35 Combine like terms: -35 + 35 = 0 0 + 7u = 63 + 35 7u = 63 + 35 Combine like terms: 63 + 35 = 98 7u = 98 Divide each side by '7'. u = 14 Simplifying u = 14
| Y(8Y+10)=3068 | | v=y(r+b)r | | (3x-6x^2)/3x | | (n-2)/-7=10 | | 4y*5y= | | 3(2)x=96forx | | (q-10)*6=18 | | 203375=o(1+.0038) | | x/1250*100=0,9 | | 3x^2+17x+9.3=0 | | (e+1)=12*3 | | 17=x/1 | | 4m+4=68 | | x/50*100=0,9 | | x-(-4)=-2+9 | | 2k+3k=20 | | (3x+70)=(8x+10) | | 20a-19a=12 | | -1/5=y-1/10 | | =20x^2+13x+15 | | 2/x=30/(-6) | | 7(2x-1)=9x+23 | | 9v-7v=16 | | 3(4x-5y)+2y=0 | | 2(k-3)=8 | | =20x^2+13+15 | | |2x-1|=1 | | 29(b+1)-5=-2b-23b | | 4-2(3x-1)=6 | | 1/(x-3)=5x/(x^2-16) | | -5z+1=-4 | | 7(b-1)=4b+12 |